IMPACT OF POSTNATAL EDUCATION ON KNOWLEDGE OF FACTORS INFLUENCING POSTPARTUM ADAPTATION AMONG PRIMIPAROUS MOTHERS - Shatu Ishaku; Oluwatoyin A. Ogunyewo; Ishaku Hassan; Ramatu Balarabe (Universitas Airlangga, 2026)
Introduction: The postpartum period is a critical transition marked by physical, psychological, and social changes requiring mothers, particularly first-time mothers, to adapt to new maternal roles. Successful adaptation is influenced by factors such as coping strategies, self-efficacy, awareness, family support, healthcare provision, cultural norms, and relevant laws or regulations. This study examined the impact of a structured health education intervention on knowledge of factors influencing postpartum adaptation among primiparous mothers in Zaria Metropolis, Kaduna State, Nigeria. Method: A quasi-experimental nonequivalent control group design with pretest and posttest was employed between October 2021 and April 2022. A total of 130 primiparous mothers were recruited using multistage sampling. The intervention group received a 40-minute structured health education session, while the control group received routine care. Data were collected using a structured questionnaire assessing knowledge of factors influencing postpartum adaptation. Analysis was conducted using descriptive statistics and McNemar’s chi-square test at p ≤ 0.05. Percentage change (Δ%) was used to estimate effect size. Result: Baseline differences were observed in age (p = 0.003) and education (p = 0.001), while other variables were comparable. The intervention group showed significant improvements across all factors (p < 0.001), with increases ranging from +3.5% to +66.5%. Notable gains were observed in knowledge of healthcare provider support (+40.8%) and laws/regulations (+66.5%). In contrast, the control group showed inconsistent changes, including declines in coping strategies (−16.7%) and personality traits (−11.8%), with no improvement in self-efficacy and legal knowledge. Overall, the intervention group demonstrated markedly greater improvement. Conclusion: Structured postnatal education significantly improves mothers’ knowledge of factors influencing postpartum adaptation. Keywords: factors; impact; postnatal education; postpartum adaptation; primiparous mothers